The Accuracy of Magnetic Resonance Imaging in Diagnosing Malignant Breast Lesions - Marriam Rasheed, Shazmeera Urooj, Sana Fatima, Naima Mujahid, Tahir Mehmood Shakir, Maheen Jamil (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The present research seeks to examine the diagnostic accuracy of magnetic resonance spectroscopy in the diagnosis of malignant breast lesions using histopathology as the gold standard. Study Design: Cross-sectional Place and Duration: Sadiq Abassi Hospital Bahawalpur. July-21 to Dec-21 Methods: There were 110 females were presented in this study. Patients had with suspicious palpable lesions for malignancy were included. Before any patient data was collected, they signed a permission form acknowledging they understood the risks. The kinetics and morphology of magnetic resonance spectroscopy (MRS) dynamically enhanced pictures acquired with contrast on 1.5 Tesla MRI equipment were evaluated. The choline peak (Cho) permitted by MRS was used to determine a malignancy biomarker.. Single-voxel approach was used to examine MRS’ diagnostic performance in breast lesions malignancy. Comparing MRS and biopsy results was done. This version of SPSS 22.0 was used to analyse all the data. Results: Majority of the patients 50 (45.5%) were from age group 41-60years, 35 (31.8%) patients had age > 60 years and 25 (22.7%) were from age group 20-40 years. Frequency of malignant lesion by MRS was found among 92 (83.6%) cases and by histopathological results its frequency was 81 (73.6%). Ductal enhancement and peripheral enhancement were the most common morphology among patients of malignant lesion by MRS. According to MRS findings, 75% specificity,86.7% accuracy, 91%sensitivty, 79% negative predictive value (NPV) and 92.3% positive predictive value were found. Conclusion: As a main imaging tool for the diagnosis of breast lesion malignancy, MRS must be used because of its superior specificity, sensitivity, and accuracy in the characterisation of breast lumps. It has been discovered that MRS is a very specific, sensitive, and reliable diagnostic tool for detecting malignant breast cancers.